The influence of catur guru on a person's intentions: a literature review from an economic perspective - Wijaya, Bagus Kusuma; Permana, I Putu Hendika (JUSTBEST Journal of Sustainable Business and Management, 2025)
This study aims to explore the influence of Catur Guru a central ethical and spiritual concept in Balinese Hindu tradition on individual economic intentions. Catur Guru comprises four respected figures: Guru Swadyaya (God), Guru Wisesa (government), Guru Pengajian (teachers/lecturers), and Guru Rupaka (parents). Using an exploratory qualitative literature review approach, this research examines how values passed down by each of these "gurus" shape economic intentions such as the intent to engage in entrepreneurship, saving, investing, purchasing, and working. Findings reveal that religiosity, trust in government, the role of educators, and family support significantly contribute to forming economic intentions, either directly through normative teachings or indirectly through the internalization of values. This study highlights the importance of integrating local slot zeus cultural values into behavioral economics research and public policy development. By deepening the understanding of Catur Guru’s influence, this review aims to support the development of context-sensitive and sustainable strategies that promote ethical and productive economic behaviors within Balinese society.